Lymphomatoid granulomatosis with rare manifestations. Case report - Pedro Rosales Torres; Pedro León Acosta (Acta Médica del Centro)
Introduction: lymphomatoid granulomatosis is a very rare disease; This is the first case reported in the hospital. Patient information: 44-year-old male, with a health history and no toxic habits, who began with respiratory symptoms, dermatological lesions, constitutional syndrome and flaccid paraplegia. Complementary examinations showed pancytopenia, and the chest x-ray and tomography showed an image suggestive of lung metastasis; An MRI showed a compressive lesion at the dorsal level. The anatomopathological studies of the skin and lung showed a lymphomatoid granulomatosis with medullary invasion. The patient was treated with chemotherapy and died abruptly one month after it began. Conclusions: lymphomatoid granulomatosis is a rare disease currently considered a lymphoid neoplasm associated with Epstein-Barr virus and large B cell lymphoma. It occurs in this patient accompanied by neurological injury; The diagnosis was only possible by anatomopathological studies. It was impossible to perform an autopsy due to family refusal.